Teknik Pembelajaran Ilmu Nahwu Berdasarkan Teori Integrasi - Ronny Mahmuddin; Chamdar Nur (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This study aims to describe the implementation of techniques or steps in learning Arabic rules (Nahwu science) based on Integration theory (Unity theory), namely that learning Arabic rules is presented in full by teaching four Arabic language skills and three language elements. The purpose of this study is also to offer solutions in the learning of integral and holistic Nahwu science.The research method is a library method with descriptive qualitative research type. The results of this study indicate that there are six steps (techniques) of teaching Arabic rules (Nahwu science) on Integration theory (Unity theory) that combines learning Arabic rules, Arabic language skills, and elements language elements in one integrated discussion material.